The Attorney's Authority in Conducting Wiretapping of The Corruption Crimes - Romli Said Ali; Muhamad Sadi Is; Belmento Belmento (Faculty of Law, University of Merdeka Malang, 2023)
The goal to be achieved in this paper is an analysis of efforts to prevent and eradicate criminal acts of corruption in the Attorney General's Office must have additional authority to carry out wiretapping because the Attorney's authority in wiretapping corruption in the Prosecutor's Law of the Republic of Indonesia has not yet been regulated. The problems that occur include the attorney's authority to tap acts of corruption regulated in another law, namely the Electronic Transaction Information Law. The method used is normative legal research. The result of the discussion is that the prosecutor's authority in wiretapping corruption in the future is to revise the Attorney General's Law of the Republic of Indonesia, which gives the prosecutor's authority in wiretapping corruption for the sake of the effectiveness and efficiency of the Attorney's performance, because the accuracy of wiretapping results can be accounted for, as well as optimizing the handling of corruption cases by the Attorney Great.How to cite item: Ali, Romli Said, Muhammad Sadi Is, and Belmento. â€œThe Attorney's Authority in Conducting Wiretapping of The Corruption Crimes.â€ Jurnal Cakrawala Hukum. 14 no. 1 (2023):Â 54-62. DOI: 10.26905/idjch.v14i1.9079.